Genome-Wide Identification of Myxobacterial Predation Genes and Demonstration of Formaldehyde Secretion as a Potentially Predation-Resistant Trait of Pseudomonas aeruginosa - Sutton, Daryn; Livingstone, Paul G.; Furness, Eleanor; Swain, Martin T.; Whitworth, David E. (Frontiers in Microbiology, 2019)
Despite widespread use in human biology, genome-wide association studies (GWAS) of bacteria are few and have, to date, focused primarily on pathogens. Myxobacteria are predatory microbes with large patchwork genomes, with individual strains secreting unique cocktails of predatory proteins and metabolites. We investigated whether a GWAS strategy could be applied to myxobacteria to identify genes associated with predation. Deduced proteomes from 29 myxobacterial genomes (including eight Myxococcus genomes sequenced for this study), were clustered into orthologous groups, and the presence/absence of orthologues assessed in superior and inferior predators of ten prey organisms. 139 ‘predation genes’ were identified as being associated significantly with predation, including some whose annotation suggested a testable predatory mechanism. Formaldehyde dismutase (fdm) was associated with superior predation of Pseudomonas aeruginosa, and predatory activity of a strain lacking fdm could be increased by the exogenous addition of a formaldehyde detoxifying enzyme, suggesting that production of formaldehyde by P. aeruginosa acts as an anti-predation behaviour. This study establishes the utility of bacterial GWAS to investigate microbial processes beyond pathogenesis, giving plausible and verifiable associations between gene presence/absence and predatory phenotype. We propose that the slow growth rate of myxobacteria, coupled with their predatory mechanism of constitutive secretion, has rendered them relatively resistant to genome streamlining. The resultant genome expansion made possible their observed accumulation of prey-specific predatory genes, without requiring them to be selected for by frequent or recent predation on diverse prey, potentially explaining both the large pan-genome and broad prey range of myxobacteria.